A Low-Cost Portable Cutting Machine for Sustainable Utilization of Sugar Palm Residues: Design, Fabrication, and Performance Analysis - Riza Muhida; Muhammad Riza; Erry Y T Adesta; Mochamad Ibnu Safari; Maman Abdurohman; Rifki Muhida; Ari Legowo (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2026)
This article presents a comprehensive exploration of innovative research and advancements in the area of mechanical engineering and advanced materials, contributing to International Journal of Innovation in Mechanical Engineering and Advanced Materials, Published by Universitas Mercu Buana. The title of a manuscript should be concise, accurately describe the contents, and not exceed 12 words. Authors (and co-authors) names are written below the title of the manuscript, without including their titles or degrees. Authors’ affiliations are written below the names. The manuscript must include an abstract written in a single paragraph, describing its main points within 200 - 300 words in English language. The abstract should briefly summarize the key elements of the research. Begin with a concise introduction to the problem or question addressed in the study, highlighting its relevance to modern technology. Clearly state the objectives, methodology, and scope of the research project. Provide a brief overview of the theoretical framework or innovative concepts explored in the paper. Discuss the practical implications of the findings and their significance in advancing the field of mechanical engineering and advanced materials. If applicable, mention key aspects such as design, construction, operation, and environmental considerations. Highlight the interdisciplinary nature of the research, emphasizing its relevance to related branches of mechanical engineering. Conclude the abstract by summarizing the main outcomes or contributions of the study. The abstract should be informative, engaging, and convey a clear sense of the paper's value to the journal's readership. Keep the language concise and avoid unnecessary technical jargon, ensuring accessibility to a broad audience interested in cutting-edge developments in mechanical engineering and advanced materials. Keywords consisting of 3-5 words or phrases which are important, specific, or representative to the article separated by semicolons should be placed immediately below the abstract.